Pengaruh Perbandingan Konsentrasi Asam Sitrat Dan Asam Malat Terhadap Karakteristik Granul Effervescent Bunga Telang (Clitoria ternatea L.) - Rachma Putri, Audrey Sophia; Ari Yusasrini, Ni Luh; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 11 No 4 (2022): Jurnal ITEPADO - 10.24843/itepa.2022.v11.i04.p18, 2022)
The purposes of this research was to determine the effect of concentration ratio of citric acid and malic acid on the characteristics of the effervescent granule of butterfly pea flower and to proper concentration ratio of citric acid and malic acid to get the effervescent granule of butterfly pea flower with the best characteristics. The research used Completely Randomized Design (CRD) with the treatment of concentration ratio of citric acid and malic acid consisting of 5 levels: 5% : 25%, 10% : 20%, 15% : 15%, 20% : 10%, dan 25% : 5%. The treatment was repeated 3 times in order to obtain 15 experimental units. The data obtained were then analyzed statistically using analysis of variance and if the treatment had a significant effect on the observed parameter, then continued with Duncan's Multiple Range Test. The results showed that the comparison of concentrations of citric acid and malic acid had a very significant effect (P < 0.01) on pH, dissolution time, flow time, foam height, total flavonoid, and antioxidant activity and significantly effect (P < 0.05) on water content. Treatment 25% citric acid : 5% malic acid was the best treatment, with the characteristics of the granul effervescent including water content 5.40%, pH 6.26, total flavonoids 7.35 mg/100g, antioxidant activity 24.15%, dissolving time 12.73 seconds, flow time 2.29 seconds, foam height 2.33 cm, as well as sensory assessments of color, aroma, taste, and overall acceptance liked.